2023
DOI: 10.3390/plants12101935
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fungal Volatile Organic Compounds for Control the Plant Parasitic Nematode Meloidogyne incognita

Abstract: Plant parasitic nematodes are a serious threat to crop production worldwide and their control is extremely challenging. Fungal volatile organic compounds (VOCs) provide an ecofriendly alternative to synthetic nematicides, many of which have been withdrawn due to the risks they pose to humans and the environment. This study investigated the biocidal properties of two fungal VOCs, 1-Octen-3-ol and 3-Octanone, against the widespread root-knot nematode Meloidogyne incognita. Both VOCs proved to be highly toxic to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…For instance, 1‐octen‐3‐ol and 3‐octanone could lead to more than 80% mortality of RKNs, but the nematicidal activity depended on the concentration of compounds 12 . 1‐octen‐3‐ol had strongly ovicidal activity, which was regarded as potential soil fumigants 25 . In line with these studies, we found that 3‐methyl‐1‐butanol caused high mortality of J2s (~70%) during the VOCs fumigant bioassay, and also caused about 70% mortality during the direct contact bioassay, while the inhibitory effect did not increase with the concentration over 1 mg/L.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, 1‐octen‐3‐ol and 3‐octanone could lead to more than 80% mortality of RKNs, but the nematicidal activity depended on the concentration of compounds 12 . 1‐octen‐3‐ol had strongly ovicidal activity, which was regarded as potential soil fumigants 25 . In line with these studies, we found that 3‐methyl‐1‐butanol caused high mortality of J2s (~70%) during the VOCs fumigant bioassay, and also caused about 70% mortality during the direct contact bioassay, while the inhibitory effect did not increase with the concentration over 1 mg/L.…”
Section: Discussionmentioning
confidence: 99%
“…12 1-octen-3-ol had strongly ovicidal activity, which was regarded as potential soil fumigants. 25 In line with these studies, we found that 3-methyl-1-butanol caused high mortality of J2s (∼70%) during the VOCs fumigant bioassay, and also caused about 70% mortality during the direct contact bioassay, while the inhibitory effect did not increase with the concentration over 1 mg/L. Accordingly, 3-methyl-1-butanol might be a good candidate for RKNs control via multiple strategies, including inhibiting egg hatching, chemotaxis response, fumigant-and contact nematicidal activity.…”
Section: Nematicidal Activity Of Vocsmentioning
confidence: 99%
See 1 more Smart Citation